Kivy : interactive applications and games in Python : create responsive cross-platform UI/UX applications and games in Python using the open source Kivy library. - Ulloa, Roberto (Community experience distilled., 2015)
If you are a Python developer who wants to create exciting and dynamic UI/UX applications that are compatible with multiple platforms, then this is the book for you. No prior experience with Kivy is required, although you should be familiar with Python and have a fair understanding of software engineering concepts such as inheritance, classes, and instances.